The Effect of Tax Socialization and Incentives on Tax Compliance of Msmes with Tax Knowledge as Intervening (Case Study on MSMEs in Tangerang City) - Siti Hawa; Parlindungan Dongoran (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Tax compliance has always been a severe problem in a country, including Indonesia; tax socialization and tax-intensive facilities provided by the government are expected to increase Compliance with taxpayers. In addition to the variables mentioned in this study, tax knowledge is also included as an intervening variable which aims to determine the extent of the influence of socialization, tax incentives and also to find out whether tax knowledge can mediate the relationship between tax socialization and tax incentives on the Compliance of MSME actors in Tangerang City. . The method used is quantitative, the sample is taken by distributing questionnaires to MSME actors in the city of Tangerang, the data analysis technique uses thePath Analysis Modeling the form of a statistical analysis method which is the development of the multiple linear regression method with the help software the SmartPLS3.0 which includes evaluation of the measurement model (outer model), evaluation of the structural model (inner model) and hypothesis testing (bootstrapping)., from the analysis results obtained that tax socialization and tax incentives have a positive and significant effect and tax knowledge can mediate the relationship between tax socialization and tax incentives on tax compliance of MSME actors in the city of Tangerang